Learning Strategies for Saxophone Instruments for Music Study Program Students ISI Yogyakarta Batch 2022 - Andhika Perdana Zebua; Boy Lamris I Simamora; Bowie Putra Bayu Mukti; Ezra Deardo Purba (Grenek: Jurnal Seni Musik, 2023)
The ISI Yogyakarta music study program currently refers more to the study of art. This resulted in a reduction in the study period for major instruments for students to 3 semesters. The music study program which focuses more on music studies targets students to become researchers and writers, so that the ability to play music is not too much considered when selecting new student admissions. Many students have shifted their instrument focus to other instruments they are not good at. The author focuses on saxophone instrument students class of 2022, most of whom experience this. This study aims to observe and describe the strategies and learning processes for the saxophone instrument course for students of the ISI Yogyakarta music study program class of 2022. The method used is qualitative-descriptive, with data collection through direct observation and interviews with students and supporting lecturers. Several lists of questions have been prepared and will serve as a tool for data collection. The author also made direct observations of the learning process carried out by lecturers and students in the saxophone instrument course. The research findings regarding the learning strategies applied are the design of a new syllabus consisting of several points to be presented to students as well as the establishment of good relationships and interactions between students and lecturers to create a comfortable learning atmosphere. The syllabus refers to the old syllabus which was previously carried out for 6 semesters, but now it is condensed into 3 semesters.